POSSIBILITIES OF CLINICAL LABORATORY EVALUATION OF ANTIPLATELET THERAPY EFFECTIVENESS IN PATIENTS WITH ISCHEMIC HEART DISEASE - O. V. Sirotkina; A. B. Laskovets; A. S. Lipunova; L. B. Gaykovaya; S. A. Boldueva; T. V. Vavilova (Столичная издательская компания, 2015)
Aim. To evaluate the functional activity of platelets by the optical standard aggregatometry and induced flow cytofluorometry during antiplatelet therapy with clopidogrel and acetylsalicylic acid (ASA). Material and methods. The evaluation of platelet function in 30 patients with ischemic heart disease treated with dual antiplatelet therapy (ASA and clopidogrel) was performed by two methods: the standard photometric method with the assessment of degree of light transmission at the maximum point and by the original method of induced flow cytofluorometry with the platelet activity evaluation by changing of glycoprotein (GP) IIb/IIIa receptor level and the expression of P-selectin before and after ADP induction. Results. Increase in platelet functional activity was detected in patients with ASA monotherapy at initial evaluation by both induced flow cytofluorometry and standard photometric method. After one month dual antiplatelet therapy platelet function significantly decreased according to standard photometric method (from 61.4Ѓ}3.6 to 45.9Ѓ}3.7; p<0.05; the induction of 2.5 mM ADP), as well as according to flow cytofluorometry with changing of GP IIb/IIIa receptor level (from 12.2Ѓ}0.8% to 5.2Ѓ}0.8%; p<0.05) and the expression of P-selectin (from 70.5Ѓ}5.9% to 57.4Ѓ}5.9%; p<0.05). Conclusion. The combined use of laboratory methods to assess platelet function (traditional and high-tech) provides cardiologist with additional tool for assessing the effectiveness of antiplatelet therapy in patients with ischemic heart disease.